Oxygen-enriched oleic matrix (NovoX) for wound healing in pediatric patients undergoing open surgical treatment for pilonidal disease: Preliminary experience - Bisol, Marta; Tykhomyrova, Sophia; Pagliara, Camilla; Scarpa, Maria-Grazia; Guida, Edoardo; Olenik, Damiana; Codrich, Daniela; Schleef, Jürgen; Boscarelli, Alessandro (Frontiers in Pediatrics, 2022)
INTRODUCTION: Pilonidal disease (PD) is a common infectious and inflammatory condition affecting the gluteal cleft and sacrococcygeal region. The optimal treatment for PD remains controversial. While the open technique reduces the number of relapses compared to minimally invasive approaches, it is associated with a longer healing time. Reactive oxygen species are a key part of the normal wound-healing process. Herein, we reported our preliminary experience using a new oxygen-enriched oil-based product called NovoX for wound healing after open surgery for PD. MATERIALS AND METHODS: We used a new oxygen-enriched product for wound healing in three pediatric patients undergoing open surgical repair for PD between December 2021 and April 2022. During postoperative follow-up, healing time and the aesthetic result were evaluated. RESULTS: Our preliminary study included three patients with chronic PD. The average follow-up time was five weeks, corresponding to the end of the healing process and the resumption of normal daily activities. Only one mild complication occurred during the study period. No short-term side effects were reported. The cosmetic result was reported as satisfactory. CONCLUSIONS: NovoX is easy to apply, safe, and effective for treating pediatric patients undergoing open surgical treatment for PD, leading to slightly faster wound healing with good aesthetic outcomes.